MULTIATTRIBUTE DECISION MAKING PENENTUAN AKREDITASI SMA MENGGUNAKAN METODE ECKENRODE DAN DIA - Yeffriansjah Salim (Lambung Mangkurat University, 2020)
The accreditation of a high school education institution (SMA) has been carried out by BAN-SM of South Kalimantan Province in stages starting from the provincial level as a recommendation provided to the national level as the decision-maker for determining accreditation. The accreditation implementation process is carried out manually. This process is carried out by both assessors and secretariat staff in charge of receiving and checking accreditation documents and reporting document inspection results and real conditions in the field that often experience fatigue and missing data. These constraints can cause the accreditation process's objectivity and even the possibility of